Leaf nonstructural carbohydrate concentrations of understory woody species regulated by soil phosphorus availability in a tropical forest. Issue 15 (14th July 2020) - Mo, Qifeng; Chen, Yiqun; Yu, Shiqin; Fan, Yingxu; Peng, Zhongtong; Wang, Wenjuan; Li, Zhi'an; Wang, Faming
Abstract: Leaf soluble sugars and starch are important components of nonstructural carbohydrates (NSCs), which are crucial for plant growth, development, and reproduction. Although there is a large body of research focusing on the regulation of plant NSC (soluble sugars and starch) concentrations, the response of foliar NSC concentrations to continuous nitrogen (N) and phosphorus (P) addition is still unclear, especially in tropical forests. Here, we used a long‐term manipulative field experiment to investigate the response of leaf NSC concentrations to continuous N and P addition (3‐, 5‐, and 8‐year fertilization) in a tropical forest in southern China. We found significant species‐specific variation in leaf NSC concentrations in this tropical forest. Phosphorus addition dramatically decreased both leaf soluble sugar and starch concentrations, while N addition had no significant effects on leaf soluble sugar and starch concentrations. These results suggest that, in plants growing in P‐limiting tropical soil, leaf NSC concentrations are regulated by soil P availability rather than N availability. Moreover, the negative relationships between NSC concentrations and leaf mass per area (LMA) revealed that NSCs could supply excess carbon (C) for leaf expansion under P addition. This was further supported by the increased structural P fraction after P fertilization in our previous study at the same site. We conclude that soil P availability strongly regulates leaf starch and soluble sugar concentrations in the tropical tree species included in this study. The response of leaf NSC concentrations to long‐term N and P addition can reflect the close relationships between plant C dynamics and soil nutrient availability in tropical forests. Maintaining relatively higher leaf NSC concentrations in tropical plants can be a potential mechanism for adapting to P‐deficient conditions. Abstract : Maintaining relatively higher leaf NSCs in tropical plants can be a potential mechanism adapting to the P‐deficient conditions. The response of leaf NSCs pool to long‐term N and P addition can reflect the tight relationships between plan C dynamic and soil nutrient availability in tropical forests.